2019
DOI: 10.7717/peerj.6217
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and virulence genes of clinical and environmental isolates ofPseudomonas aeruginosa

Abstract: Background Pseudomonas aeruginosa is ubiquitous, has intrinsic antibiotic resistance mechanisms, and is associated with serious hospital-associated infections. It has evolved from being a burn wound infection into a major nosocomial threat. In this study, we compared and correlated the antimicrobial resistance, virulence traits and clonal relatedness between clinical and fresh water environmental isolates of P. aeruginosa.Methods219 P. aeruginosa isolates were studied: (a) 105 clinical isolates from 1977 to 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 67 publications
4
14
0
Order By: Relevance
“…The results indicated that the isolates were susceptible to both ciprofloxacin 13 (100%) and norfloxacin 12 (92.3%), while completely resistant to ampicillin, bacitracin, erythromycin, streptomycin, tetracycline, trimethoprim-sulfamethoxazole, and tobramycin, most of the isolates were resistant to amikacin, chloramphenicol, and gentamycin. These findings agreed with the other previous studies which illustrated that the organism is resistant to all used antibiotics except quinolones [32-35].…”
Section: Resultssupporting
confidence: 93%
“…The results indicated that the isolates were susceptible to both ciprofloxacin 13 (100%) and norfloxacin 12 (92.3%), while completely resistant to ampicillin, bacitracin, erythromycin, streptomycin, tetracycline, trimethoprim-sulfamethoxazole, and tobramycin, most of the isolates were resistant to amikacin, chloramphenicol, and gentamycin. These findings agreed with the other previous studies which illustrated that the organism is resistant to all used antibiotics except quinolones [32-35].…”
Section: Resultssupporting
confidence: 93%
“…The analyzed samples in this study were found in different anatomical sites such as urinary, respiratory and auditive tract, wounds from different parts of the body, in addition to bloodstream samples. P. aeruginosa was mainly isolated from the respiratory and urinary tract, as well as from wounds, in consistence with other studies where they have also been found in these sites and wounds of severely burnt patients [30]. Regarding antibiotic resistance, in this The abbreviations correspond to the origin and code of the strains, labeled with each of the sampling site of the isolate) UC, urine culture, RTS, respiratory tract secretions, BAL, bronchoalveolar lavage, E, ear, W, wound.…”
Section: Discussionsupporting
confidence: 82%
“…The environmental antimicrobial susceptible P. aeruginosa strains are also infectious for human but it is likely that they become resistant during the infection, possibly with the influence of antimicrobial therapy pressure [ 14 ]. A growing number of reports on the increased virulence of multi-drug resistant P. aeruginosa isolates, when compared to more susceptible strains, can be found in the available literature [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been recently shown that particular resistance mechanisms can easily and favorably co-exist with virulence genes in particular sets of strains [ 13 , 21 , 22 ]. Other authors, on the contrary, have suggested that the virulence of antibiotic-resistant P. aeruginosa strains (including carbapenem-resistant isolates) has somehow been reduced [ 16 , 17 , 18 , 19 ]. One of the explanations of this phenomenon is that bacterial cells somehow selectively activate genes, when necessary from the survival point of view, while silencing other ones.…”
Section: Discussionmentioning
confidence: 99%